2014
DOI: 10.1016/j.molonc.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

miR181b is induced by the chemopreventive polyphenol curcumin and inhibits breast cancer metastasis via down‐regulation of the inflammatory cytokines CXCL1 and ‐2

Abstract: Curcumin Breast cancer Inflammatory cytokines microRNAs A B S T R A C TChronic inflammation is a major risk factor for the development and metastatic progression of cancer. We have previously reported that the chemopreventive polyphenol Curcumin inhibits the expression of the proinflammatory cytokines CXCL1 and -2 leading to diminished formation of breast and prostate cancer metastases. In the present study, we have analyzed the effects of Curcumin on miRNA expression and its correlation to the anti-tumorigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 55 publications
1
109
0
2
Order By: Relevance
“…Furthermore, it was mirrored that decreased miR‐181b restrained vascular remodelling by activating TGF‐β/pSmadD2/3 pathway,40 and addition of angiotensin II into cardiac fibroblasts could significantly down‐regulate miR‐181b expression 41. In addition, it has been illuminated that miR‐181b might suppress breast cancer cells’ capacity of metastasis by targeting CXCL1 and CXCL2, a couple of inflammatory cytokines 42, 43, 44. He et al45 arrived at conclusions that miR‐181b was highly expressed with prostate cancer tissues and cell line (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was mirrored that decreased miR‐181b restrained vascular remodelling by activating TGF‐β/pSmadD2/3 pathway,40 and addition of angiotensin II into cardiac fibroblasts could significantly down‐regulate miR‐181b expression 41. In addition, it has been illuminated that miR‐181b might suppress breast cancer cells’ capacity of metastasis by targeting CXCL1 and CXCL2, a couple of inflammatory cytokines 42, 43, 44. He et al45 arrived at conclusions that miR‐181b was highly expressed with prostate cancer tissues and cell line (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Kronski et al found that miR181b-mediated CXCL1 and -2 expression through direct binding to 3'UTR that mediated curcuminrelated down-regulation of CXCL1 and -2 in breast cancer cells (MDA-MB-231) (53). They also suggested that miR181b induces apoptosis and inhibits the expression of MMPs in vitro, thus inhibiting invasion of cancer cells.…”
Section: Curcumin Regulates Micrornas (Mirnas) Expressionmentioning
confidence: 99%
“…Therefore, miRNAs regulate cellular proliferation, differentiation and apoptosis, closely associated with cancer (51-53). miRNAs regulate several proteins' expressions by binding to mRNA three prime untranslated region (3'UTR), which then degrades mRNA or inhibits mRNA translation (53). miRNAs have a dual effect in cancers, either acting as tumor promoters or tumor suppressors (53).…”
Section: Curcumin Regulates Micrornas (Mirnas) Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that miR-22 was upregulated upon curcumin treatment, and the predicted targets were ERα and transcription factor Sp1, while miR-196, an oncogenic miRNA in gastric cancers, was significantly downregulated after curcumin treatment [61] . Curcumin has been shown to downregulate putative oncogenic miRNAs, such as miR-21 [62,63] , while it upregulates key tumor-suppressor miRNAs, including miR-200 family, let-7 family, miR-185b, and miR-22 [64,65,66] . More recently, Toden and colleagues reported that curcumin chemosensitizes colorectal cancer cells to 5-fluorouracil (5FU) by suppression of epithelial-mesenchymal transition (EMT) through upregulation of EMT-suppressive miRNAs in 5-fluorouracil resistant (5FUR) cell lines.…”
Section: Curcuminmentioning
confidence: 99%